2020
DOI: 10.1186/s43058-020-00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the pragmatic measurement of sustainment: a narrative review of measures

Abstract: Background Sustainment, an outcome indicating an intervention continues to be implemented over time, has been comparatively less studied than other phases of the implementation process. This may be because of methodological difficulties, funding cycles, and minimal attention to theories and measurement of sustainment. This review synthesizes the literature on sustainment measures, evaluates the qualities of each measure, and highlights the strengths and gaps in existing sustainment measures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 73 publications
1
58
0
Order By: Relevance
“…The influences and strategies to promote an EBP’s sustainment may be unique or distinct from influences and strategies that are effective in previous stages and thus require additional tools and research approaches [ 7 , 8 ]. Despite acknowledgement of the importance of sustainment, there are multiple reasons why this final phase of the implementation process is less well studied, one of which being a lack of valid, easily accessible, pragmatic measures of sustainment that are appropriate for direct service providers [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The influences and strategies to promote an EBP’s sustainment may be unique or distinct from influences and strategies that are effective in previous stages and thus require additional tools and research approaches [ 7 , 8 ]. Despite acknowledgement of the importance of sustainment, there are multiple reasons why this final phase of the implementation process is less well studied, one of which being a lack of valid, easily accessible, pragmatic measures of sustainment that are appropriate for direct service providers [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a number of published measures of sustainment and sustainability, existing measures tend to address sustainability rather than sustainment and tend to focus on community public health programs (e.g., smoking cessation campaigns) rather than specific EBPs implemented at an organizational level [ 8 ]. In addition, a recent review of published measures of sustainment and sustainability found existing measures tend to be time-intensive, require stakeholders across multiple levels or stakeholders with knowledge across multiple levels to complete, and tend to be limited to assessing a particular EBP or only appropriate for a specific setting [ 9 ]. As an example, recently, a 35-item Sustainment Measurement System Scale (SMSS) [ 11 ] was published to assist Substance Abuse and Mental Health Services Administration (SAMHSA)-funded preventative programs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, adoption (corresponding to the Implementation phase of the EPIS framework) was defined as having started an MRT group after the initial training, and the adoption phase as the time period in which there was active support for the implementation of MRT (see “Training Program Overview” section). Sustainment was defined as maintenance of MRT after the active support ended (Moullin et al 2020 ). Accordingly, we (1) estimated the prevalence of MRT adoption and sustainment across VHA facilities, (2) identified facility characteristics associated with MRT adoption and sustainment, and (3) used qualitative approaches to understand the facilitators and barriers to sustainment of MRT across facilities.…”
Section: Introductionmentioning
confidence: 99%